Computers from the Perspective of Social Philosophy - Gray L. Dorsey (Washington University Law Quarterly, 1977)
Assuming computers to be an extremely important technology in a post-industrial society, we need a sense of what society is, and of the basic interrelationships between society, technology, law, science, and ethics. A functional, evolutionary context will serve the purpose. In this Article, Professor Dorsey suggests that the computer will replace production machinery as the essential technology. Computers will enable us to anticipate the future effects of scientific discoveries so that we may better control our society. With computers, we can simulate the values, obligations, and institutions that would be appropriate in a society that encouraged a particular scientific discovery. We can then determine at the outset whether a certain course of action will permit a more satisfying life or destroy the human spirit. Thus, Professor Dorsey believes the computer will provide the means with which we can intelligently direct and control, rather than be engulfed by, the age of information.
Keywords: Computing and the Law